ANALYSIS OF THE AGRICULTURAL LABOUR FORCE IN TERMS OF THE AREA CULTIVATED WITH THE MAIN CROPS IN ROMANIA, DURING THE PERIOD 20 8-2022 - Cătălina-Nicoleta COMAN; Răzvan PANAIT; Cristiana Silvia BUZATU; Cosmina Andreea SMEDESCU; Nicoleta Florica PĂTRĂCHIOIU; Valentina-Constanța TUDOR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
At a time when expert analysts states that one of the main reasons why Romanian agriculture has been going through a major crisis for more than a decade is the labor crisis in agriculture, this article will examine the evolution of the areas cultivated with major crops and of the agricultural labor force from 20 8 to 2022. The study will cover the entire country, the 8 development regions, and the 7 counties within the South-Muntenia development region, also indicating the total area under main crops per person employed in agriculture during the reference period. To create this article, statistical data have been analyzed using the data from the National Institute of Statistics of Romania, TEMPO Online database, and using both descriptive and inferential statistics. In the year 2022, the area cultivated with the main crops in Romania slightly exceeded 8 million hectares. In the same year, out of 7.8 million people with an income-generating occupation, only about % of these people had an occupation in agriculture, thus a person employed in agriculture had a little over 9 ha of the total cultivated area with the main cultures.